Recurrent Sepsis Exacerbates CD4+ T Cell Exhaustion and Decreases Antiviral Immune Responses - He, Wanxue; Xiao, Kun; Xu, Jiaruo; Guan, Wei; Xie, Sheling; Wang, Kaifei; Yan, Peng; Fang, Min; Xie, Lixin (Frontiers in Immunology, 2021)
Sepsis is a life-threatening organ dysfunction caused by a dysregulated host response to an infection. It is a disease with a high incidence, mortality, and recurrence rate and frequently results in its survivors requiring readmission into hospitals. The readmission is mainly due to recurrent sepsis. Patients with recurrent sepsis are more susceptible to secondary infections partly due to immune dysfunction, leading to a higher mortality in the long term. However, there remains a gap in the understanding of immunological characteristics and underlying mechanisms of recurrent sepsis. In this study, we used mouse models of acute and recurrent sepsis to investigate their different immunological characteristics. And then we subjected the two mouse models to a secondary influenza A virus (H1N1) infection and characterized the different immune responses. Here, we demonstrated that CD4+ T cells present an exacerbated exhaustion phenotype in response to recurrent sepsis as illustrated by the decreased frequency of CD4+ T cells, reduced co-stimulatory CD28 and increased inhibitory PD-1 and Tim-3 expression on CD4+ T cells, increased frequency of regulatory T cells, and reduced MHC-II expression on antigen-presenting cells. Moreover, we showed that antiviral immune responses decrease in the recurrent sepsis mouse model subjected to a secondary infection as illustrated by the reduced pathogen clearance and inflammatory response. This may be a consequence of the exacerbated CD4+ T cell exhaustion. In summary, recurrent sepsis exacerbates CD4+ T cell exhaustion and decreases antiviral immune responses, contributing to significant morbidity, increased late mortality, and increased health care burden in recurrent sepsis patients.